Two new combinations in Lysiphyllum (Leguminosae-Caesalpinioideae) - Bandyopadhyay, Subir; Ghoshal, Partha Pratim (Phytotaxa, 2014)
Two new combinations in Lysiphyllum (Benth.) de Wit for species earlier treated in Bauhinia L. are made. The typification of Bauhinia diptera Blume ex Miq. is explored.